LE NUOVE FRONTIERE DELL’ARCHEOLOGIA DALLA FOTOGRAFIA AEREA AL TELERILEVAMENTO SATELLITARE SAR - Dore, Nicole; Patruno, Jolanda (Archeomatica, 2012)
Il grande progresso tecnologico ha dato la possibilità a campi di indagine più tradizionali, come l'archeologia, di usufruire di tecnologie per trarne il massimo vantaggio ai fini di indagini preventive sul campo. È sulla sciadi conquiste come il telerilevamento satellitare ottico ad alta risoluzione spaziale, che la presente ricerca si è spinta oltre tali confini, con lo scopo di indagare la tecnica polarimetrica SAR (Synthetic Aperture Radar). New Frontiers in Archaeology. From Aerial Photography to Satellite Remote Sensing SAR This work is part of an ongoing PhD project held at the Area di Geodesia e Geomatica – University ofRome ‘La Sapienza'. The work involves the study of archaeological sites through the analysis of polarimetric L-band data from the PALSAR sensor (on the Japanese ALOS satellite, launched in May 2006) with the aim of understanding the spectral signature of archaeologicalremains (above and below ground). The Italian sites of Vulci (VT)and Arpi (FG), analyzed through polarimetric imagery, were chosen according to the availability of polarimetric SAR data at the time of the study and to the different geomorphologic characteristics of theterrain, with the purpose of observing the scattering mechanisms associated to the features present in the scene.